Factors affecting cost overrun at construction projects in Somalia - Osman, Yusuf Hussein (2019)
The construction industry plays an influential role in the socio-economy of a country. In Somalia, the construction industry is one of the essential industries participating significantly in the growth of socio-economic development. Somalia is facing a significant issue of cost overrun in construction projects. The issue of cost overrun has become a serious concern to investors, which needs serious attention and in-depth research to put forward solutions to this issue. The objectives of this research are (1) To identify factors causing cost overrun in construction projects, (2) To study a strategy to overcome cost overrun in construction projects. The research was taking place in Somalia. And it is based on quantitative research by using questionnaire to carry out the research. The questionnaire was designed based on the objectives. A total of 51 questionnaires were gathered from a total of 100 Grade A contractors in Somalia. The analysis of the data was used by using SPSS software. The variables of this research were ranked based on their mean; the study proves that the contractors are facing cost overrun problems specifically the factors used in the questionnaire. Furthermore, majority of the respondents strongly agreed to the strategies provided by the study to overcome cost overrun and keep the construction projects within budget. This finding contributes to the contractor’s development and could be referenced by contractors who want to increase their chance of overcoming cost overruns in construction projects.